2019
DOI: 10.3390/s19051114
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent and Dynamic Ransomware Spread Detection and Mitigation in Integrated Clinical Environments

Abstract: Medical Cyber-Physical Systems (MCPS) hold the promise of reducing human errors and optimizing healthcare by delivering new ways to monitor, diagnose and treat patients through integrated clinical environments (ICE). Despite the benefits provided by MCPS, many of the ICE medical devices have not been designed to satisfy cybersecurity requirements and, consequently, are vulnerable to recent attacks. Nowadays, ransomware attacks account for 85% of all malware in healthcare, and more than 70% of attacks confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…In this dramatic scenario, the authors of [10] identified critical shortcomings of ICE in challenging scenarios such as security, quality of service (QoS), and high availability. To improve the previous aspects, the authors of [11] presented an architecture, called ICE++, for the MEC paradigm that combined SDN/NFV. As an extension of ICE++, proposed ML-based solution able to classify several well-known families of ransomware affecting the medical devices of ICE.…”
Section: Cybersecurity In Icementioning
confidence: 99%
“…In this dramatic scenario, the authors of [10] identified critical shortcomings of ICE in challenging scenarios such as security, quality of service (QoS), and high availability. To improve the previous aspects, the authors of [11] presented an architecture, called ICE++, for the MEC paradigm that combined SDN/NFV. As an extension of ICE++, proposed ML-based solution able to classify several well-known families of ransomware affecting the medical devices of ICE.…”
Section: Cybersecurity In Icementioning
confidence: 99%
“…Moreover, ML based malware detection methods were discussed. Furthermore, Fernandez Maimo et al (Fernandez Maimo et al 2019) used ML techniques for detecting and classifying ransomware attacks in ICE. The NFV/SDN methods were used to isolate and remove contaminated medical equipment and networks.…”
Section: Tablementioning
confidence: 99%
“…IoT and CC are service computing platforms that allow object interconnection, including personal and sensitive data, over wireless channels [29,30,31]. The collective data of physical objects or sensors is generally stored on a cloud-server [32,33,34,35].…”
Section: System Modelsmentioning
confidence: 99%